An Assessment of Indonesia’s Monetary Integration with Oil Exporter Countries in Islamic Nations: Evidence from Panel Data - Agustiar, Memet (International Journal of Energy Economics and Policy, 2019)
The paper aims to assess the monetary integration between Indonesia and oil exporting countries in Islamic countries. Increasing the oil trade intensity between Indonesia and oil-producing countries can drive monetary integration among them. This study applies the Optimum Currency Area (OCA) index to measure the degree of monetary integration between Indonesia and 21 oil-producing countries in the OIC. The results exhibit that the majority of oil-producing countries are strongly integrated with Indonesia. The panel regression test highlights two variables – the inflation similarity and trade openness – which had a significant effect on the OCA. This study provides an important policy base for Indonesia, primarily in improving its relations with oil-producing countries. Two channels – trade openness and maintaining harmonious price stability – are the entry point for Indonesia to integrate with oil countries. Keywords: Monetary integration; Optimum Currency Area; Islamic nations; Indonesia; oil countries. JEL Classifications: E42, F36, F33 DOI: https://doi.org/10.32479/ijeep.8420